Assessment of the influence of vitamin D in patients with sepsis: a systematic review and meta-analysis - Zhu, Hangqi; Li, Keyi; Zhao, Yulu; Qin, Juan; Song, Guolin (Frontiers in Nutrition, 2025)
BackgroundThis systematic review and meta-analysis seeks to extensively estimate the interrelation between vitamin D (VD) and clinical results among both pediatric and adult sepsis patients.MethodsA search was implemented through four databases (PubMed, Embase, Cochrane Library, and Web of Science) up to February 2025. Meta-analysis was implemented utilizing Stata 15 and Meta-Disc software.ResultsThirty-nine studies were included, encompassing 1,208 pediatric and neonatal sepsis patients, and 60,566 adult sepsis patients. The results showed that the average VD level in neonates with sepsis was 12.99 (95% CI: 8.11, 17.87), and the average VD level in children was 24.84 (95% CI: 21.34, 28.33). Their VD levels were considerably lower relative to healthy individuals or those without sepsis, with statistical distinction (p < 0.05). The aggregated prevalence of VD deficiency and insufficiency was 54%. When VD levels were <30 ng/mL, the aggregate prevalence of deficiency and insufficiency was the highest at 76%. A considerable interrelation between VD deficiency and mortality was identified, contrasted with the control group (p < 0.05). Among adults with sepsis, the average VD level was 17.12 (95% CI: 14.19, 20.05). Relative to the healthy cohort, VD levels substantially declined, with statistical distinction (p < 0.05); relative to those without sepsis, there was no statistical distinction in VD levels (p = 0.05). The pooled prevalence of VD deficiency and insufficiency was 55%. The deficiency of VD was considerably correlated with both the incidence and mortality of sepsis (p < 0.001). Supplementation with VD did not reduce the length of ICU stay (p = 0.67), but it can considerably reduce the risk of death (p < 0.05). The sensitivity and specificity of VD to forecast mortality among adult sepsis patients were 81 and 31%, respectively.ConclusionVitamin D status in both pediatric and adult sepsis individuals was predominantly in a deficient state, and the prevalence of VD deficiency and insufficiency is relatively high. VD deficiency was considerably linked to elevated mortality among pediatric sepsis individuals and also the incidence and mortality of adult sepsis individuals. VD may serve as a valuable biomarker to forecast mortality among adult sepsis individuals.Systematic review registrationhttps://www.crd.york.ac.uk/PROSPERO/view/CRD420250651346, CRD420250651346